Polar Views on the Arctic: Arctic Policies of Russia and Circumpolar Countries - E. A. Korchak (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2019)
The article discusses current issues of Arctic governance. The main motives of the growing interest of the world community to this region are revealed. Comparative analysis of the conceptual framework and key priorities of the Arctic policy of the Russian Federation and other circumpolar powers based on a study of their national Arctic strategies. It was determined that the main difference between the Russian model of managing the Arctic zone lies in the priority of exploitation of natural resources on the basis of creating an optimal configuration of the main factors of industrial production, while the policy of foreign northern countries is aimed primarily on the sustainable development of the Arctic territories and at achieving their social sustainability through the comprehensive development of Arctic local communities. In our opinion, it is advisable for the Russian Federation to apply such a model where the state vector of Arctic policy is oriented, first of all, to the social component of territorial development as for the basis for a comprehensive balanced development of the Arctic zone and for ensuring the country’s national security. Namely, – the implementation of the model of sustainable development of the Arctic territories, the main elements of which are rational and careful nature resource use in the Arctic zone, limitation of negative environmental impact and conservation of the biodiversity of the Arctic territories, orientation on the national policy not only on the indigenous peoples of the North, but also on the local population living here, improving the quality, conditions and standard of living, as well as close mutually beneficial international cooperation on municipal, regional and global levels.